Binding Interactions between the Encephalomyocarditis Virus Leader and Protein 2A - Petty, Ryan V. (J Virol, 2014)
The leader (L) and 2A proteins of cardioviruses are the primary antihost agents produced during infection. For encephalomyocarditis virus (EMCV), the prototype of the genus Cardiovirus, these proteins interact independently with key cellular partners to bring about inhibition of active nucleocytoplasmic trafficking and cap-dependent translation, respectively. L and 2A also bind each other and require this cooperation to achieve their effects during infection. Recombinant L and 2A interact with 1:1 stoichiometry at a K(D) (equilibrium dissociation constant) of 1.5 μM. The mapped contact domains include the amino-proximal third of 2A (first 50 amino acids) and the central hinge region of L. This contact partially overlaps the L segment that makes subsequent contact with Ran GTPase in the nucleus, and Ran can displace 2A from L. The equivalent proteins from Theiler's murine encephalomyelitis virus (TMEV; BeAn) and Saffold virus interact similarly in any subtype combination, with various affinities. The data suggest a mechanism whereby L takes advantage of the nuclear localization signal in the COOH region of 2A to enhance its trafficking to the nucleus. Once there, it exchanges partners in favor of Ran. This required cooperation during infection explains many observed codependent phenotypes of L and 2A mutations. IMPORTANCE Cardiovirus pathogenesis phenotypes vary dramatically, from asymptomatic, to mild gastrointestinal (GI) distress, to persistent demyelination and even encephalitic death. Leader and 2A are the primary viral determinants of pathogenesis, so understanding how these proteins cooperate to induce such a wide variety of outcomes for the host is of great important and interest to the field of virology, especially to those who use TMEV as a murine model for multiple sclerosis.